New mites of the genus Holoparasitus Oudemans, 1936 from northern Austria and Karavanke (Acari: Parasitidae) - Witaliñski, Wojciech (Zootaxa, 2006)
A new mite species, Holoparasitus rhombogynialis sp. nov. (Acari: Parasitidae) is described from Karavanke (Slovenia-Austria border). H. hemisphaericus (Vitzthum, 1923) is redescribed, including a description of the previously unknown male from the type locality in northern Austria. Both species are considered to be members of the Holoparasitus hemisphaericus species-group, which is newly defined. Ologamasus absoloni Willmann, 1940 is synonymised with H. hemisphaericus, and the female of H. intermedius (Holzmann) sensu Micherdziński is synonymised with H. cornutus Juvara-Bals & Witaliński.